ANALISIS PROTEKSI KEBAKARAN PADA PERUSAHAAN PRODUKSI GAS DAN PEMBANGKIT LISTRIK - Bery Romadhon (Universitas Airlangga, 2018)
PT. Gresik Gases Indonesia and PT. Gresik Power Indonesia is a company engaged in the production of gas and power plants with natural gas and diesel power. This production site has a potential fire hazard so it must be implemented active and passive fire protection system. This research held to determine the suitability of active fire protection systems, passive in the workplace based on with several standards such as the SNI 03-3985-2000, NFPA 13, Permenaker no. 04/1980, Permen PU no. 26/PRT/M/2008, SNI 03-1745-2000. Observational data collection used regulated checklists, with cross-sectional research design. This production site was the potential for serious hazards to cause large area fire and in a short time. Classification of fire in this production of type A, B, C were derive from fuel oil storage tanks, T 80 C, T 80 D, MCC 20 KV, SHEQ and admin office, ware house, gas compressor area, gas engines, combustion turbine, control room, centrifuge pump, and regent heater. Active fire protection was several assessments such as alarm, detector, sprinkler, exhaust, and hydrant. On passive fire protection, the assessment was based on buildings. Field observations obtained the following results active protection system such as alarm with enough categories, detector with enough categories, sprinkler with enough categories, a fire extinguisher with a good category, hydrants with good categories and on passive fire protection systems with sufficient category.Keywords: fire protection, gas production, power plant